2017
DOI: 10.14740/jocmr2763w
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Vibration Training During a Low Frequency Outpatient Exercise Training Program in Chronic Obstructive Pulmonary Disease Patients: A Randomized, Controlled Trial

Abstract: BackgroundThe aim of the study was to investigate whether whole-body vibration training (WBVT) can be applied beneficially within an outpatient low frequency exercise program.MethodsIn a prospective, controlled, randomized study, WBVT effectiveness and safety were investigated in COPD stage II-IV patients undergoing a 3-month training program. Participants took part in a 90-min circuit training once a week. On top patients were randomized to either perform squats with WBVT, or without (conventional training gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 27 publications
2
19
0
3
Order By: Relevance
“…With analysis from three included trials, 9 , 12 , 13 no significant difference was found between the two groups regarding the CAT score (WMD: 1.35 points, 95% CI: −1.56 to 4.27, P =0.36) and the change of CAT score (WMD: −0.29 points, 95% CI: −3.27 to 2.69, P =0.85).…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…With analysis from three included trials, 9 , 12 , 13 no significant difference was found between the two groups regarding the CAT score (WMD: 1.35 points, 95% CI: −1.56 to 4.27, P =0.36) and the change of CAT score (WMD: −0.29 points, 95% CI: −3.27 to 2.69, P =0.85).…”
Section: Resultsmentioning
confidence: 86%
“…A total of 1,012 studies were identified by the initial database search. Only eight RCTs 6 13 with 365 patients were included in our study after full evaluation ( Figure 1 ). The included studies were published between 2012 and 2017.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations